The skull of StW 573, a 3.67 Ma Australopithecus prometheus skeleton from Sterkfontein Caves, South Africa. Issue 134 (September 2019) - Clarke, Ronald J.; Kuman, Kathleen
Abstract: Here we present the first full anatomical description of the 3.67 million-year-old Australopithecus skull StW 573 that was recovered with its skeleton from the Sterkfontein Member 2 breccia in the Silberberg Grotto. Analysis demonstrates that it is most similar in multiple key morphological characters to a group of fossils from Sterkfontein Member 4 and Makapansgat that are here distinguished taxonomically as Australopithecus prometheus . This taxon contrasts with another group of fossils from those sites assigned to Australopithecus africanus . The anatomical reasons for why these groupings should not be lumped together (as is frequently done for the South African fossils) are discussed in detail. In support of this taxonomy, we also present for the first time a newly reconstructed palate of A. africanus (StW 576 from Sterkfontein Member 4), which has a uniquely complete permanent dentition. The StW 573 skull also has certain similarities with other earlier Australopithecus fossils in East Africa, assigned to Australopithecus afarensis and Australopithecus anamensis, which are discussed. One of its most interesting features is a pattern of very heavy anterior dental wear unlike that found in A. africanus but resembling that found in A. anamensis at 4.17 Ma. Because the StW 573 skull is associated with a near-complete skeleton that is also described for the first time in this special issue, we are now able to use this individual to improve our understanding of more fragmentary finds in the South African fossil record of Australopithecus .